The Influence of Company Capital, Wage Levels, and Production Value on Increasing the Availability of Employment in Makassar City - Mustari, Mustari (Cita konsultindo, 2023)
This study aims to determine the effect of increasing the availability of employment in Makassar City, especially at the pharmacy company partner blessing light. The method used is a qualitative method. Data collection techniques are by conducting interviews, direct observation, and literature/literature studies. Data analysis was carried out by describing the results of interviews and analyzing the findings. From the results of this study, it was found that the effects of company capital, wage levels, and production value on increasing the availability of employment at partner pharmacies, blessing light.